Human gut bacteria produce TH17-modulating bile acid metabolites - Paik, Donggi; Yao, Lina; Zhang, Yancong; Bae, Sena; D’Agostino, Gabriel D.; Zhang, Minghao; Kim, Eunha; Franzosa, Eric A.; Avila-Pacheco, Julian; Bisanz, Jordan E.; Rakowski, Christopher K.; Vlamakis, Hera; et al. (Nature (London), 2022)
The microbiota modulates gut immune homeostasis. Bacteria influence the development and function of host immune cells, including T helper cells expressing interleukin-17A (TH17 cells). We previously reported that the bile acid (BA) metabolite 3-oxolithocholic acid (3-oxoLCA) inhibits TH17 cell differentiation1. While it was suggested that gut-residing bacteria produce 3-oxoLCA, the identity of such bacteria was unknown, and it was unclear whether 3-oxoLCA and other immunomodulatory BAs are associated with inflammatory pathologies in humans. Here, we identify human gut bacteria and corresponding enzymes that convert the secondary BA lithocholic acid into 3-oxoLCA as well as the abundant gut metabolite isolithocholic acid (isoLCA). Like 3-oxoLCA, isoLCA suppressed TH17 differentiation by inhibiting RORγt (retinoic acid receptor-related orphan nuclear receptor γt), a key TH17 cell-promoting transcription factor. Levels of both 3-oxoLCA and isoLCA and the 3α-hydroxysteroid dehydrogenase (3α-HSDH) genes required for their biosynthesis were significantly reduced in inflammatory bowel disease (IBD) patients. Moreover, levels of these BAs were inversely correlated with expression of TH17 cell-associated genes. Overall, our data suggest that bacterially produced BAs inhibit TH17 cell function, an activity that may be relevant to the pathophysiology of inflammatory disorders such as IBD.